Behavioral health service use post‐jail release and reduced risk of return to jail. Issue 7 (7th February 2022) - Smith, Joseph L.; Khatri, Utsha G.; Olubiyi, Oluwatoyin; Hadley, Trevor; Lim, Suet; Mandell, David; Kang‐Yi, Christina
Abstract: This study examined whether behavioral health service use post‐jail release was associated with reduced risk of jail reincarceration. The study sample included 20, 615 individuals who had behavioral health diagnoses and were released from the Philadelphia County jail. Using administrative records of the county jail and state‐, county‐, and Medicaid‐funded behavioral health service use from 2010 to 2018, we conducted Cox proportional hazard analyses to estimate the association between behavioral health service use post‐jail release and the risk of return to jail within 3 years. Nearly 50% of the sample returned to jail within 3 years. Individuals who used behavioral health services were 26%–38% less likely to return to jail within 3 years than were individuals who did not. The study results suggest that connecting individuals with behavioral health services upon release from jail can reduce the risk of repeated jail incarceration.